Analisis Permasalahan Implementasi Kurikulum 2013 - Yohannes Telaumbanua (Politeknik Negeri Padang, 2014)
The curriculum is at the core of education and have an influence on the entire educational activities. Given the importance of the curriculum in education and human life the curriculum can not be done are not measurable and not systematic. Curriculum requires a philosophical foundation historical sociological psychological powerful precise theories of learning knowledge and experience of teachers and support infrastructure in the PBM adequate education. The design of curriculum development in 2013 has met the demands of the progress of globalization and rapid information systems today. In fact the design of the curriculum is notyet supported by the knowledge and experience of teachers in implementing the 2013 curriculum to students for example the first taskof analyzing the SKL KI KD Books Students and teachers book has not been fully carried out by teachers much remains to copy andpaste and lack of time to read the document in depth and the concept of a scientific approach is still not understood let alone on learning methods that are less applicable delivered. Furthermore educational infrastructure for the benefit of the PBM has not beenable to keep teachers teaching and students learning inside and outside the classroom